Cognitive Biases in Search as Learning: Bridging Conceptual Foundations and Empirical Research - Machado, Marcelo; Souza, Jairo F. de; Siqueira, Sean W. M. (Anais Estendidos do Congresso Brasileiro de Informática na Educação (CBIE); 2025: Anais Estendidos do XIV Congresso Brasileiro de Informática na Educação, 2025)
Online search is a key part of how people learn, yet it is not a neutral process. Cognitive biases shape how users search for, select, and interpret information. While the Search as Learning (SAL) field studies how people learn throughout the search process, it has not yet integrated research on cognitive biases. This paper bridges that gap by proposing a conceptual model and an experimental framework that connect SAL with cognitive bias research. We conducted a real-world experiment on confirmation bias, involving learners searching for “The use of AI in education”. It showed how prior beliefs influence search behaviors. This work advances both the theoretical understanding and empirical study of biases in SAL, supporting the development of fairer, more transparent, and educationally effective search technologies.